Assessing community awareness and participation in health facility governing committees in two districts of Tanzania: a cross-sectional study - Hussein Athuman Kapuya; Stephen Oswald Maluka; Anna-Karin Hurtig; Miguel San Sebastian (Archives of Public Health)
Abstract Background Tanzania has been promoting community participation in health, either directly or through health facility governing committees (HFGCs), as part of its wider, ongoing health system reforms since the 1990s. Although some studies have assessed the functioning of the HFGCs, little is known about community knowledge and involvement in their activities. Methods A cross-sectional survey assessing community awareness and participation in HFGCs was conducted between July and October 2022, involving two rural districts of Tanzania, which were selected based on their performance: Handeni, showing low performance and Mbarali, high performance. A total of 1,184 household heads living in the catchment areas of diverse facilities were involved. Frequencies and percentages were calculated overall and by district. The Chi-squared test was applied to assess statistically significant differences in knowledge, awareness, and participation between the districts. Results The results revealed that 85.3% of the participants were unaware of the presence of the HFGCs and 91.7% did not know their roles. Additionally, 87% had neither heard nor seen any announcement about the selection of committee members. Only 14.5% considered that HFGCs were accountable to the community. While 96.7% of the respondents said they had never received any feedback from the HFGCs, only 8.1% reported that HFGCs were collecting views from the community. Regarding participation, 79.9% believed that the community had not been supporting their activities; however, 44.7% believed that the committees were important in improving health service delivery. Feedback and support were more common in Handeni. Conclusion The level of community awareness of and participation in HFGCs was very low in both districts. The Ministry of Health and the President’s Office of Regional Administration and Local Government should implement an action plan to raise community awareness of the role of the HFGCs and their significance in promoting social accountability within the Tanzanian health system.